Agriculture Students' Cultural Understanding During Students' Exchange in Kampus Merdeka Program: A Literature Review Approach - Dyah Gandasari (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study investigates the role of the Kampus Merdeka Program in promoting cross-cultural understanding in the context of agriculture during students' exchange. By employing a literature review as the methodological approach, the study synthesizes existing scholarly works to analyze the effectiveness of international exchange programs in fostering intercultural learning within the agricultural domain. The review delves into various aspects, including the impact of cultural immersion, communication barriers, and the significance of intercultural competence in the context of agricultural education. The findings aim to shed light on the benefits of cross-cultural experiences in agricultural learning environments, paving the way for future enhancements in the Kampus Merdeka Program and similar initiatives worldwide.